The Economic Impact of a Pilot Digital Day-Case Pathway for Knee Arthroplasty in a U.K. Setting. Issue 1 (24th January 2023) - Cooper, D.M.; Bhuskute, N.; Hepworth, C.; Walsh, G.
Abstract : Background: Knee replacements are an increasingly common procedure in the U.K. National Health Service (NHS). Importantly, the pathway for such procedures represents a prime opportunity to leverage digital technology, modernize and streamline the approach to care, and free up resources. Methods: In this 21-patient pilot study, we assessed the impact of implementing a digital day-case pathway for knee replacement surgery at the Calderdale and Huddersfield NHS Foundation trust. Results: Fourteen (67%) of the 21 eligible patients were treated as day cases, with an average length of stay of 8.8 hours. The pilot data were utilized to model the potential impact of implementing a digital day-case program more widely across the trust. This model showed increased efficiency over the entire episode of care, with reductions in physiotherapy appointments, preoperative visits, hospital days, and face-to-face consultations. Not only would these improvements free up capacity, but they would also result in an estimated saving of £240, 540 to the trust while reducing the CO2 footprint of knee replacements by 119, 381 kg CO2 emitted. A sensitivity analysis revealed that, even with substantial variation of several key variables within the pathway, a trust-wide digital day-case program would still be a cost-saving measure. Conclusions: Overall, the present study supports the growing notion that digital technology can facilitate the transformation of care pathways, resulting in greater efficiency and financial savings for health-care providers while reducing the time patients spend in the hospital. Level of Evidence: Therapeutic Level II . See Instructions for Authors for a complete description of levels of evidence.